Mathematics Teachers’ Technological Pedagogical and Content Knowledge and their Capacity for Differentiated Instruction - Patalinghug, Joey S.; Arnado, Alvic A. (Future Science / FSH-PH Publications, 2021)
The primary goal of this study was to determine the trainings in the teachers’ learning and development for differentiated instruction to enhance the instructional strategies of the elementary school teachers in North Butuan District of the Division of Butuan City, Agusan del Norte. The participating teachers completed the TPACK survey which consisted of the demographic profile of teachers and the TPACK components namely: Technology Knowledge (TK), Content Knowledge (CK), Pedagogical Knowledge (PK), Pedagogical Content Knowledge (PCK), Technological Content Knowledge (TCK), Technological Pedagogical Knowledge (TPK), Technology Pedagogy and Content Knowledge (TPACK) and Differentiated Instruction survey instrument about mathematics. In addition, both surveys were analyzed based on how the teachers performed in TPACK and differentiated instruction and percentage of the capacity of teachers based on the two different methods of teaching. Among the four components of TPACK, the technological knowledge, content knowledge, pedagogical knowledge, and pedagogical content knowledge, pedagogical knowledge had the highest mean. The level of differentiated instruction of the participants in terms of lesson design and implementation revealed that learning activities are varied got the highest mean. In addition, the differentiated instruction in terms of lesson design and implementation, content, procedures, communication and learning were found to have the highest mean. Teachers teaching elementary mathematics may be requested to attend webinars on TPACK or related seminars/webinars to enhance their knowledge in dealing with the content in mathematics specifically word problems and their concerns on differentiated instruction.